The Veterinary Profession in Greece. Review of the Present and Prospects for the Future. Ill Vetarinary education: Scools and specialirations. B. Specializations of direct interest - ΧΑΤΖΗΟΛΟΣ ΒΑΣΙΛΕΙΟΣ Κ. (Journal of the Hellenic Veterinary Medical Society, 2019)
The improvement and expansion of education in recent years necessitated by the tremendous development and progress of science in the various fields created the need for comprehensive knowledge in new disciplines and for uncovering ways and means to solve urgent problems. Thus, new specializations emerged carrying with them obligations to increase and improve studies and research in new scientific fields. Many of today’s specializations have a direct bearing on the veterinary profession, either because their subjects constitute part of the veterinary responsibility per se, or they are closely related to it, or the need for veterinarians in these specializations is urgent, or because they offer possibilities for further profitable studies and research. Nine of these specializations form the subject of this paper. They are: (1) Animal Science, (2) Development of Experimental Animals and Veterinary Care, (3) Public Health, (4) Military Veterinary Service, (5) Toxicology, (6) Radiation, (7) Veterinary Clinical Sciences, (8) Diseases of Exotic and Tropical Countries, and (9) Veterinary Medicine of Wild Animals. The purpose, opportunities, and education required for each of the Above specialization is discussed.